Suppression Method of AC-Stark Shift in SERF Atomic Magnetometer - Yang Li; Ming Ding; Xuejing Liu; Hongwei Cai; Junpeng Zhao; Jiancheng Fang (IEEE Photonics Journal)
In a spin-exchange-relaxation-free (SERF) atomic magnetometer with ultrahigh sensitivity, the ac-Stark shift generated by circularly polarized light results in the attenuation of the SERF atomic magnetometer response, and the virtual magnetic field gradient induced by the ac-Stark shift can reduce the sensitivity of the SERF atomic magnetometer. In this paper, we use a hybrid optical pumping method to address the ac-Stark shift problem. By switching between left-hand and right-hand circularly polarized lights and compensating the residual magnetic field of the magnetometer, the ac-Stark shift could be reduced and then suppressed effectively.